The Effect of Resveratrol on the Composition and State of Lipids and the Activity of Phospholipase A2 During the Excitation and Regeneration of Somatic Nerves - Revin, Victor Vasilevich; Pinyaev, Sergey Ivanovich; Parchaykina, Marina Vladimirovna; Revina, Elvira Sergeevna; Maksimov, Georgiy Vladimirovich; Kuzmenko, Tatyana Pavlovna (Frontiers in Physiology, 2019)
It has been shown that in the somatic nerve’s lipids, both during excitation and transection, changes occur with the composition of individual phospholipids and in phospholipids fatty acids, which changes the phase state of the myelin and nerve fiber axolemma lipid bilayer. A main contribution in the nerve degenerative processes is dependent on the composition phospholipid’s fatty acid changes during the activation of both Ca2+-dependent and Ca2+-independent phospholipase A2 forms. At the same time, we studded changes in phosphoinisitol (PI) and diacylglycerol (DAG), which depend on the phosphoinositide cycle function during nerve excitation and degeneration processes. It was found that myelin lipids and nerve fiber axolemmas are involved not only in the functioning of the peripheral nerves, but also the pathological processes underlying deep functional and structural disorders. The effect of resveratrol on regeneration processes in the damaged rat sciatic nerve has also been investigated.